Efeitos do treinamento físico com kettlebell sobre a qualidade de movimento, força muscular e capacidade cardiorrespiratória - Castro, Bruno Farias (2016)
Since it was introduced in the United States in 2001, Kettlebell training has grown exponentially among professional and amateur athletes from different sports. The main argument used by disseminators of this methodology was the fact that their ballistic exercises would be efficient to generate positive adaptations in muscle strength and power and cardiorespiratory endurance simultaneously, as well as being an extreme energy consumption activity. Such statements are currently supported by respected scientific publications however; it is not yet scientifically clear whether there is different adaptations between the two most common ways of practicing the swing, a fundamental exercise in Kettlebell training. Just as it´s unclear what is the best dose to prescribe for each goal during kettlebell training. Two studies were then developed with the following objectives: a) to compare the two most common forms of execution of the swing exercise, unilateral and bilateral (study one); b) to compare two typical kettlebell training routines with different volume and intensity (study two). Participated in this research physically active university students without experience (study one) or experience (study two) in kettlebell training. The results of our studies suggest that: a) the two forms of the swing exercise, unilateral and bilateral, are effective to improve the quality of motion muscle strength and cardiorespiratory endurance; b) Regardless of the volume and intensity used in the protocol of this study, the total training load was primarily responsible for the significantly positive response in the quality of movement, strength and cardiorespiratory endurance.